Aligning micro-gripper to ring object in high precision with microscope vision - Juan Zhang; Zhengtao Zhang; De Xu; Wensheng Zhang (2011 IEEE International Conference on Computer Science and Automation Engineering, 2011)
In this paper, a platform based on microscope vision is established to align and grip a ring object. An effective alignment algorithm is proposed based on a microscope vision system in order to realize the gripping in high precision. The multiple features of the micro-gripper in the image such as the edge length and the circle center are detected to regulate the microscope vision system. The desired position and orientation of the ring object is determined according to the features of the micro-gripper in the image captured by the horizontal camera. The ring object's pose is adjusted to the desired pose above. Once the ring object's pose coincides with the micro-gripper's pose, the micro-gripper is moved to the ring object under the visual guidance of the vertical camera and grips it. Experimental results demonstrate the effectiveness of the alignment algorithm.